컨볼루션 신경망을 이용한 도시 환경에서의 안전도 점수 예측 모델 연구 - 강현우; Hyeon-woo Kang; 강행봉; Hang-bong Kang (정보처리학회 논문지 (KTSDE), 2016)
최근, 컴퓨터 비전과 기계 학습 기술의 도움을 받아 효율적이고 자동적인 도시 환경에 대한 분석 방법의 개발에 대한 연구가 이루어지고 있다. 많은 분석들 중에서도 도시의 안전도 분석은 지역 사회의 많은 관심을 받고 있다. 더욱 정확한 안전도 점수 예측과 인간의 시각적 인지를 반영하기 위해서, 인간의 시각적 인지에서 가장 중요한 전역 정보와 지역 정보의 고려가 필요하다. 이를 위해 우리는 전역 칼럼과 지역 칼럼으로 구성된 Double-column Convolutional Neural Network를 사용한다. 전역 칼럼과 지역 칼럼 각각은 입력은 크기가 변환된 원 영상과 원 영상에서 무작위로 크로핑을 사용한다. 또한, 학습 과정에서 특정 칼럼에 오버피팅되는 문제를 해결하기 위한 새로운 학습방법을 제안한다. 우리의 DCNN 모델의 성능 비교를 위해 2개의 SVR 모델과 3개의 CNN 모델의 평균 제곱근 오차와 상관관계 분석을 측정하였다. 성능 비교 실험 결과 우리의 모델이 0.7432의 평균 제곱근 오차와 0.853/0.840 피어슨/스피어맨 상관 계수로 가장 좋은 성능을 보여주었다. Recently, there have been various researches on efficient and automatic analysis on urban environment methods that utilize the computer vision and machine learning technology. Among many new analyses, urban safety analysis has received a major attention. In order to predict more accurately on safety score and reflect the human visual perception, it is necessary to consider the generic and local information that are most important to human perception. In this paper, we use Double-column Convolutional Neural network consisting of generic and local columns for the prediction of urban safety. The input of generic and local column used re-sized and random cropped images from original images, respectively. In addition, a new learning method is proposed to solve the problem of over-fitting in a particular column in the learning process. For the performance comparison of our Double-column Convolutional Neural Network, we compare two Support Vector Regression and three Convolutional Neural Network models using Root Mean Square Error and correlation analysis. Our experimental results demonstrate that our Double-column Convolutional Neural Network model show the best performance with Root Mean Square Error of 0.7432 and Pearson/Spearman correlation coefficient of 0.853/0.840.